Dimanakah Keadilan bagi Mesir? Kritik Ideologi Keluaran 1:1-22 dan Relevansinya bagi Perjuangan Keadilan di Aitinyo, Papua Barat Daya - Sharon Manuhua; Margaretha M.A Apituley (Program Pascasarjana UKIM, 2024)
Giving a negative perspective to other groups today is an action that can often be found. This is also the case for the people of Papua, especially Aitinyo, Southwest Papua. The text Exodus 1:1-22 is one of the texts that illustrates a similar problem. Starting from these two problems, this article aims to examine the ideology of Exodus 1:1-22 and dialogue it with the present context. The process of interpretation is done by using the method of ideological criticism from the perspective of indigenous people. In the analysis conducted, it is known that the one-sided depiction of the group is also displayed by the author of Exodus 1:1-22, where the author of the text describes Egypt as the perpetrator of violence in his narrative for the sake of each group of writers. All the historical data that can be collected then provides an important understanding to fight for justice and improve the perspective of Egypt and Aitinyo.